Business Analyst : Careers in business analysis - Reed, Adrian (BCS Guides to IT Roles Ser., 2018)
This practical guide explores the business analyst role including typical responsibilities and necessary skills. It signposts useful tools and commonly used methodologies and techniques. A visual career roadmap for business analysts is also included, along with case studies and interviews with practising business analysts.